Participating in a support group: experience lived by women with breast cancer - Cleoneide Paulo Oliveira Pinheiro (Revista Latino-Americana de Enfermagem, 2008)
The goal of the study was to understand the meaning of support groups in the life of women with breast cancer. It is a qualitative study with 30 mastectomized women who belonged to six support groups in the city of Fortaleza, Ceará. Data were collected with semi-structured interviews, organized and analyzed based on the interactionism concept. The results characterized the support groups as a mechanism to cope with the situation and to overcome the suffering derived from the diagnosis and treatment of the breast carcinoma. The socialization of the experiences facilitated the search for assistance in the support groups, since sharing the problems with mastectomized women was a way to preserve a high self-esteem, have faith and overcome some difficulties. Participating in the group provided well-being and a differentiated care, since it was considered a way to know, accept and understand the disease and its cure, facilitating the socialization of ideas.